MANAJEMEN PENGELOLAAN PASAR DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH PADA DINAS PASAR DAN KEBERSIHAN KABUPATEN KEPULAUAN TALAUD - MISA, JUNALDI; RURU, JOORIE MARHAEN; PLANGITEN, NOVVA (JURNAL ADMINISTRASI PUBLIK, 2020)
The purpose of this research is to know how the management of market management in increasing thelocal revenueThe research approach used in this research is a qualitative method. Methods or techniques of dataanalysis used are interactive analysis models. The research informant as many as 10 people of thisresearch is taken from various elements directly and indirectly related to the management of themarket in the Talaud Islands regency.The results showed that the planning function did not go well, many programs and activities wereimplemented not in accordance with the plans that had been established. Management implementationby the leader has not been executed to the maximum so that many officers or employees of the marketwho do not understand what to do not get clear instructions or direction from the management of theunit. There is still misuse of power or authority in the case of the collection of retribution so there is aloss or shortage in depositing the results of the PAD to local treasury.Keywords: management, market management, indigenous revenue region